What Are the Potential Predictors of Psychological Capital for Chinese Primary School Teachers? - Chen, Xinjie; Zeng, Guang; Chang, Edward C.; Cheung, Hoi Yan (Frontiers in Education, 2019)
This study aimed to explore the cognitive and affective factors that predict the Psychological capital (PsyCap) of Chinese primary school teachers. The participants were 1384 teachers from 34 primary schools in Chengdu city, in southwestern part of China. A resource model of PsyCap was proposed and tested using structural equation modeling (SEM). The model was tested with two independent variables of growth mindset and well-being as predictors of PsyCap. Results showed that both cognitive construct (i.e. growth mindset) and affective construct (i.e. well-being) were positively and significantly related to the PsyCap. In addition, SEM results indicated a significant influence of both growth mindset and well-being on all the variables of PsyCap (i.e. Efficacy, Hope, Optimism and Resilience). Explanations and implications were discussed for the findings, and some limitations were also discussed.